Perencanaan Pembelajaran Berbasis Teaching Factory pada Kompetensi Keahlian Teknik Pemesinan di SMK Bhinneka Karya Surakarta - Ahmad Kafi; Andhika Budi Utomo; Apri Ghuntur Setyawan; Aqis Nur Kholis; Bayu Handoyo Aji; Bimo Tri Cahyanto; Budi Harjanto; Sulistyo Sulistyo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
This research aims to describe the teaching factory planning process, the use of the teaching factory application, and its assessment to improve student competency at Bhinneka Karya Surakarta Vocational School. The Teaching Factory planning design was carried out based on the results of observations and analysis at Bhinneka Karya Vocational School, Surakarta. In-depth interview techniques, observation and documentation were used to collect data. Interactive models play a role in analyzing data and procedures starting with data collection, reduction, presentation and verification of conclusions. Research findings show that the implementation of teaching factory-based learning in the context of developing student competency begins with planning, implementation of learning, production/service activities, industrial collaboration, impacts and obstacles faced. In planning the teaching factory, utilizing strategies to realize change, the material in class, titles and job sheets are adjusted to existing standards in the industry, educators adapt the practices carried out by students so that they are equipped to deliver quality material that is driven throughout the day, the talents that they will carry out. Through teaching factories, student competence can be improved with various learning procedures that have been established in the curriculum and implemented for vocational school students.